Pemberian Hadiah Pada PT BPRS Gajahtongga Kotopiliang Kota Sawahlunto - Yenni Puspita Sari; Zainuddin Zainuddin (Al-bank: Journal of Islamic Banking and Finance, 2021)
This study examines the prizes given by PT. BPRS Gajahtongga Kotopiliang City of Sawahlunto on savings and financing products. The problem in this research is that the bank's wadi’ah savings product promises to give a gift in the form of a bonus in the form of an increase in the balance and the bank also gives bonuses to customers who pay installments on time in the form of money said at the beginning of the contract. The type of research used is field research with descriptive analytical methods that use economic fiqh theory. The data sources used are primary and secondary data sources, while the data collection techniques used are interviews and documentation. The result of this research is that the gift given by PT BPRS Gajahtongga Kotopiliang in the form of a bonus to customers on the wadi'ah savings product is not yet in accordance with the DSN Fatwa NO: 86 / DSN-MUI / IX / 2012 regarding the prize in raising funds in Islamic Financial Institutions, while the provision of a loan installment bonus if the purpose is to discipline customers in paying their legal debt. However, the system for awarding bonuses is not in accordance with the provisions of prizes at Islamic Financial Institutions